Neurons in the Rat Anterior Cingulate Cortex Dynamically Encode Cost–Benefit in a Spatial Decision-Making Task - Hillman, Kristin L. (J Neurosci, 2010)
Optimal decision-making often requires an assessment of the costs and benefits associated with each available course of action. Previous studies have shown that lesions to the anterior cingulate cortex (ACC) impair cost–benefit decision-making in laboratory animals, but the neural mechanisms underlying the deficit are not well understood. We recorded from ACC neurons in freely moving rats as they performed a spatial decision-making task whereby, in the baseline configuration “2:6B,” rats could pursue two or six food pellets, the latter obtained by climbing a barrier [high cost, high reward (HCHR)]. In this configuration, the mean percentage of HCHR choices was 69 ± 4%, and a substantial portion of ACC neurons (63%) exhibited significantly higher firing for one goal trajectory versus the other; for 94% of these cells, higher firing was associated with the HCHR option. This HCHR bias was not simply attributable to the larger reward, the barrier, or behavioral preference. In intersession and intrasession manipulations involving at least one barrier (2:6B, 2B:6B, and 2:2B), ACC activity rapidly adapted and was consistently biased toward the economically advantageous option relative to the configuration. Interestingly, when only a difference in reward magnitude was presented (2:6, no barrier, HCHR choices of 84 ± 4%), ACC activity was minimal and nonbiased. One interpretation of our data is that the ACC encodes a relative, integrated cost–benefit representation of available choice options that is biased toward the “better” option in terms of effort/outcome ratio. This representation may be specifically recruited when an assessment of reward and effort is required to optimally perform a task.